2015
DOI: 10.1021/acs.jmedchem.5b00597
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 1-{4-[3-Fluoro-4-((3S,6R)-3-methyl-1,1-dioxo-6-phenyl-[1,2]thiazinan-2-ylmethyl)-phenyl]-piperazin-1-yl}-ethanone (GNE-3500): a Potent, Selective, and Orally Bioavailable Retinoic Acid Receptor-Related Orphan Receptor C (RORc or RORγ) Inverse Agonist

Abstract: Retinoic acid receptor-related orphan receptor C (RORc, RORγ, or NR1F3) is a nuclear receptor that plays a major role in the production of interleukin (IL)-17. Considerable efforts have been directed toward the discovery of selective RORc inverse agonists as potential treatments of inflammatory diseases such as psoriasis and rheumatoid arthritis. Using the previously reported tertiary sulfonamide 1 as a starting point, we engineered structural modifications that significantly improved human and rat metabolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…An umber of small-molecule RORgtm odulators [23] such as SR2211, [24] TMP778, [17] GSK805, [25] and GNE-3500 [26] (Figure 1) have been described and showcase the diversity of chemical structures which are ablet om odulate the receptor. [20,[27][28][29][30] The literature, including patenta pplications, has been reviewed recently.…”
Section: Introductionmentioning
confidence: 99%
“…An umber of small-molecule RORgtm odulators [23] such as SR2211, [24] TMP778, [17] GSK805, [25] and GNE-3500 [26] (Figure 1) have been described and showcase the diversity of chemical structures which are ablet om odulate the receptor. [20,[27][28][29][30] The literature, including patenta pplications, has been reviewed recently.…”
Section: Introductionmentioning
confidence: 99%
“…Fauber and co‐workers engineered compound 105 , which possessed potent, selective, and orally bioavailable retinoic acid receptor‐related orphan receptor C (RORc) inverse agonist potency in a cell assay with no distinguishable activity against any of the other RORs or NRs in the small cell panel . In a subsequent report, the same group prepared the oxa‐sultam derivatives 106 , which also acted as RORc inverse agonists and showed reduced lipophilicity, improved selectivity, and favorable ADME properties …”
Section: Use Of Sultams In Biological Fieldsmentioning
confidence: 99%
“…

An ew applicationo fP d-catalysed allylation is reported that enables the synthesis of ar ange of branched sp 3 -functionalised sulfonamides,acompound class for whichf ew reported methodse xist. [4] a-Substitution with alkyl groups can improve the bindingp roperties; [5] however,d espitet he wide interest in the exploitationof sulfonamides, many of the compounds reported bear sparse substitutionp atterns adjacent to the sulfonyl moiety.B earing this fact in mind, and in the context of the drive forl ate-stage molecular functionalisation, there has been ar ecenti nterest in the development of new methods for direct a-functionalisation of sulfonamides. The reactionw as performed under mild conditions and could be appliedt on anomolar sigma-receptor binders, thus enabling al ate-stage functionalisation and efficient expansion of drug-likec hemical space.

The difficulties in accessing non-planar "hard-to-make" chemical matter for incorporation into drug molecules have been well-enumerated, [1] and in some therapeutic areas these difficulties have significant consequences.

…”
mentioning
confidence: 99%
“…By reacting benzyl sulfonamideswith allylic acetates in the presence of Pd 0 catalysts and base at room temperature, direct allylation was efficiently performed, yielding productsthat are analogues of structural motifs seen in biologically active small molecules. However,d espite the considerable effortd irected towards synthesis of sulfonamides from readily available starting molecules, [6] there are still few generally applicable methods fort he efficient preparation of a-branched sulfonamides.Traditional methods (Figure1b) for direct alkylation of sulfonamides [7] require strong bases, reactive electrophiles, low temperatures and the use of stoichiometrica mounts of polar additives [such as tetramethylethylenediamine (TMEDA), [8] hexamethylphosphoramide( HMPA), [9] and phenanthroline [5] ]; several recentr eports have described metal-catalysed a-arylation of alkyl [10] sulfonamides (Figure 1c), [11] but only the methods from Zhou et al [11d] (who reported as ingle exampleo fb ranched sul- [a] O. Thus, there has been ad rive to delivern ew small molecules with enhanced biological relevance, and ac oncomitantc all for late-stage functionalisation [2] to enable improvements( such as the "magic methyl" effect) [3] in pharmacological properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation